Innovations and advancements in adhesives for maxillofacial prosthesis in carcinoma rehabilitated patients - N. Gopi Chander; Neha Venkat; A. Noorul Rizwana (Oral Oncology Reports)
Maxillofacial prosthetics play a crucial role in the rehabilitation of oral cancer patients, significantly enhancing their quality of life by restoring facial structure and function. The success of these prosthetics is dependent on adhesives, that ensures assured attachment and stability. Despite their significance, adhesives have received reduced attention in the literature. This review aims to meet this literature gap by exploring the innovations and advancements in adhesives for maxillofacial prosthetics.Traditional adhesives, while widely used, often fall short in terms of durability and biocompatibility, especially under the dynamic conditions of the oral cavity. Recent developments in biocompatible materials and applied technology have introduced new adhesives that offer improved adhesion strength, durability, and patient comfort. Smart adhesives, which respond to environmental stimuli like pH and temperature, present significant advancements, enhancing the adaptive nature of prosthetic attachment.Customized adhesive solutions, facilitated by digital printing of prosthesis, provide more accurate prosthesis and reduces the interfacial gap with the skin and prosthesis. This further improving prosthetic performance with a predictable layer of adhesives in the interface. Additionally, new application techniques and tools have enhanced the precision and ease of adhesive use, ensuring consistent and reliable attachment.This review highlights the importance of advanced adhesives in managing oral cancer patients, presenting the crucial role they play in the effectiveness and comfort of maxillofacial prosthetics. It also emphasizes the need for these adhesives to be a key focus in future research and clinical practice.